Konjac glucomannan-modified ferrous fumarate emulsions with interpenetrating polymer networks: Physicochemical stability, microstructure, and bioaccessibility - Tianyu Zhang; Fengru Zhang; Xintong Wang; Yuanting Wang; Mengting Jia; Zihan Ma; Yanbo Wang; Duoxia Xu (Food Hydrocolloids, 2027)

Inverse-opal g-C3N4-supported halogen-regulated Bi2WO6/Bi2SiO5/BiOClxBr1-x heterostructures for simulated-sunlight-driven antibiotic degradation - Jingyue Hu; Yuanting Wu; Mato Knez; Lihui Guo; Cuicui Wang; Hulin Liu; Xinmeng Zhang; Ou Hai; Yunlong Xue (Journal of Environmental Chemical Engineering, 2026)

Permeability evolution of coal fracture during injection-induced shear slip - Zhe Zhou; Fan Wang; Zhaolong Ge; Yuanting Zhang (Geomechanics for Energy and the Environment, 2026)

Three-dimensional spherical ordered mesoporous Al-MCM-48 solid acid catalysts for the rapid conversion of biomass-derived GVL to butene - Haibiao Yu; Yudong Li; Yuanting Du; Ruixi Yang; Weijun Shan; Yuejiao Wang; Ruan Chi; Ying Xiong (Fuel, 2026)

Robust prediction of CO2 absorption in blended amines via structure-concentration integration: A machine learning approach for imbalanced and data-scarce systems - Binmin Li; Tengxian Qin; Zehua Xu; Zhi Yang; Guiyang Ye; Jiaoying Huang; Yuanting Qiao; Xuelan Zeng; Song He; Yawen Zheng; Junyao Wang (Journal of Environmental Chemical Engineering, 2026)

Endoplasmic reticulum stress–based ATF6 signaling pathway: evaluation of 4-PBA improving retinal state in myopic guinea pigs - Mengke Wu; Miao Zhang; Mingbin Tian; Weibo Pan; Xuexin Wang; Ruixue Zhang; Yuanting Yang; Zhongyu Ma; Zhaohui Yang; Yinqiao Zhang; Hongsheng Bi; Dadong Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of oxygen vacancies induced by doping rare earth metal elements (La³⁺, Ce³⁺/⁴⁺, Nd³⁺) in NaTaO3 thin films on photocatalytic and antibacterial properties - Cuicui Wang; Shuxian Dong; Ruixue Yin; Anqi Cai; Haoyu Li; Zhizun Yue; Hongxia Ren; Chuanli Zhang; Hairong Yin; Yuanting Wu (Journal of Environmental Chemical Engineering, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Polyphenol-mediated hierarchical porous hydrogel evaporators for accelerated water transport and reduced evaporation enthalpy - Xueqian Zhang; Hongtao Li; Bo Liang; Zikun Zou; Zhen Yang; Shaohui Xiong; Lei Yang; Xu Wang; Yang Chen; Yuanting Xu; Yiwen Li (Science Bulletin, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Dynamic effects of technological innovations, research and development expenditure, and effective governance on carbon emission: New insights for environmental policy formulation in BRI region - Yuanting Xia; Dan Cao; Lingkang Wang (Journal of Environmental Management, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

A 29-year-old male with eosinophilic myocarditis and multisystem involvement: A diagnostic dilemma between EGPA and idiopathic hypereosinophilic syndrome - Shan Ma; Yanqing Hu; Shuaiye Liu; Jihua Wang; Kun Zhang; Yuanting Zhu; Yang Wu (Next Research, 2025)

Construction of inhomogeneous bismuth-based heterojunctions with efficient interfacial charge transport: Bridging of BiOX - Yuanting Wu; Lihui Guo; Xuhua Liu; Xiaoying Wang; Jingyue Hu; Yunlong Xue; Ou Hai; Hulin Liu; Xinmeng Zhang; Weizhi Tian; Yongqiang Feng (Environmental Research, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Hollow Fe2O3-NiFe2O4 hetero-nanoframes coupled with N-doped graphene for boosted electrochemical water oxidation through optimizing intermediate bonding - Yuanting Li; Ya Zhang; Ruidong Shi; Xiaoxin Xu; Xue Wang; Gongbing Zhou (Chemical Engineering Journal, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Construction of energy storage heterojunction and enhancement mechanism of dark and full-spectrum energy storage piezoelectric catalysis - Bixin Zhang; Guoqiang Tan; Wenlong Liu; Xiongtao Wu; Linxin Guo; Zeqiong Wang; Chunyan Zeng; Ying Liu; Tian Liu; Qian Yang; Ao Xia; Huijun Ren; et al. (Chemical Engineering Journal, 2025)

Transcriptome analysis of the genes and regulators involving in vitamin E biosynthesis in Elaeagnus mollis diels - Shuhui Du; Yuanting Guo; Qianqian Li; Xiaoyan Hu; Yang Tian; Baochang Cheng; Shengji Wang; Zhiling Wang; Ruifen Ren; Zhaoshan Wang (Plant Molecular Biology, 2024)

Exploring the response and prediction of phytoplankton to environmental factors in eutrophic marine areas using interpretable machine learning methods - Shimin Yang; Yuanting Ma; Jie Gao; Xiajie Wang; Futian Weng; Yan Zhang; Yan Xu (Science of The Total Environment, 2024)

Promotion of manganese on Fe-based catalyst for the production of carbon nanotubes (CNTs) from plastics - Su He; Chunchun Li; Hongman Sun; Christopher M.A. Parlett; Yuanting Qiao; Youhe Wang; Yikai Xu; Ningbo Gao; Chunfei Wu (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Roles of extracellular vesicles on macrophages in inflammatory bone diseases - Yifan Lin; Ziyan Wang; Shirong Liu; Jiaohong Liu; Zhiyi Zhang; Yuanting Ouyang; Zhikang Su; Ding Chen; Lvhua Guo; Tao Luo (Molecular and Cellular Biochemistry, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Prescribed-time observer-based sideslip compensation in USV line-of-sight guidance - Chunlai Yu; Junkang Zhu; Yuanting Hu; Hao Zhu; Ning Wang; Haohao Guo; Qinjin Zhang; Siyuan Liu (Ocean Engineering, 2024)

Asymmetric phosphorylation integrating host feature and blue thermally activated delayed fluorescence of thiaxanthene S,S-dioxide emitter for efficient heavily doped white organic light-emitting diodes - Yingying Chen; Chao Wang; Peng Ma; Yuanting Guo; Yuetong Liu; Aiqi Dang; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Thin and soft Ti3C2Tx MXene sponge structure for highly sensitive pressure sensor assisted by deep learning - Wang Guo; Zhiqiang Ma; Zhou Chen; Haojun Hua; Dong Wang; Mohamed Elhousseini Hilal; Yatian Fu; Pengyi Lu; Jian Lu; Yuanting Zhang; Derek Ho; Bee Luan Khoo (Chemical Engineering Journal, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

An ultra-high-temperature cavity receiver with a simple flat absorber for safe and efficient solar-thermal conversion - Jikang Wang; Yuanting Zhang; Yu Qiu; Qing Li (Journal of Cleaner Production, 2024)

Testosterone attenuates senile cavernous fibrosis by regulating TGFβR1 and galectin-1 signaling pathways through miR-22-3p - Zongren Hu; Yuanting Zhang; Jisong Chen; Min Luo; Neng Wang; Yinfu Xiao; Qinghu He (Molecular and Cellular Biochemistry, 2023)

Numerical Simulations of Tank Sloshing Problems Based on Moving Pseudo-Boundary Method of Fundamental Solution - Chengyan Wang; Yuanting Zou; Ji Huang; Chia-Ming Fan (Journal of Marine Science and Engineering, 2023)
The moving pseudo-boundary method of fundamental solutions (MFS) was employed to solve the Laplace equation, which describes the potential flow in a two-dimensional (2D) numerical wave tank. The MFS is known for its ease of programming and the advantage of its high precision. The solution of the boundary value can be expressed by a linear combination of the fundamental solutions. The major issue with such an implementation is the optimal distribution of source nodes in the pseudo-boundary. Traditionally, the positions of the source nodes are assumed to be fixed to keep the set of equations closed. However, in the moving boundary problem, the distribution of source nodes may influence the stability of numerical calculations. Moreover, MFS is unstable in time iterations. Hence, it is necessary to constantly revise the weighting coefficients of fundamental solutions. In this study, the source nodes were free, and their locations were determined by solving a nonlinear least-squares problem using the Levenberg–Marquardt algorithm. To solve the above least-squares problem, the MATLAB© routine lsqnonlin was adopted. Additionally, the weighting coefficients of fundamental solutions were solved as a nonlinear least-squares problem using the aforementioned method. The numerical results indicated that the numerical simulation method adopted in this paper is accurate and reliable in solving the problem of 2D tank sloshing. The main contribution of this study is to expand the application of the MFS in engineering by integrating it with the optimal configuration problem of pseudo-boundaries to solve practical engineering problems.

Toxicity effects of disinfection byproduct chloroacetic acid to Microcystis aeruginosa: Cytotoxicity and mechanisms - Jing Ye; Jiawei Ni; Fuxiang Tian; Xiyan Ji; Meifang Hou; Yuanting Li; Lei Yang; Runxiang Wang; Wenwu Xu; Liang Meng (Journal of Environmental Sciences, 2023)

Highly active and durable nitrogen-doped CoP/CeO2 nanowire heterostructures for overall water splitting - Lili Zhang; Yuanting Lei; Wenjing Xu; Dan Wang; Yafei Zhao; Wenxing Chen; Xu Xiang; Xinchang Pang; Bing Zhang; Huishan Shang (Chemical Engineering Journal, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.